Mushroom growing in Punjab: cost components, and determinants affecting its productivity - Rajdeep Singh; J M Singh (Agricultural Economics Research Review, 2023)
The study has worked out cost and return structure of white button mushroom in Punjab and has identified the determinants affecting its productivity. The study was conducted in Amritsar and Gurdaspur districts with a sample of 80 mushroom growers. The selected mushroom growers were divided into three categories on the basis of bed area spawned. The economic analysis shows that non-recurring and recurring expenditures per square metre of bed area spawned declines with increase in mushroom farmsize due to the economies of scale. The gross returns are higher on medium mushroom farms due to comparatively higher average price realization while the net returns are higher on large mushroom farms due to lower cost. The input-output ratio has been found highest (1.81) on large mushroom farms, followed by medium (1.47) and small (1.35) mushroom farms. Judicious use of pesticides, labour-use in picking, packing and casing operations are found to improve mushroom productivity. The study emphasizes on the training of growers for disinfection of mushroom growing sheds, mechanized compost preparation plant, canning and refrigeration facility.